You can’t see what you don’t measure! A scoping review of measurements of gender-based violence, its determinants and consequences in academia - Claudia Schredl; Anke Lipinsky; Anne Laure Humbert (PLoS ONE, 2025)
Introduction Assessing the problem of gender-based violence in academia internationally is challenging due to a lack of empirical evidence and differences in how it is measured. The contribution of this article is to reflect on survey measurements and to propose new avenues for future quantitative measurements of gender-based violence, its determinants, and consequences in an academic context. For this purpose, we present the results of a scoping review of ten national and cross-national prevalence studies on gender-based violence. We examined the studies’ quantitative operationalisation of (1) sex and gender, (2) prevalence of gender-based violence, (3) socio-demographic determinants from an intersectional perspective, individual and contextual factors, (4) and consequences. Materials and methods Prevalence studies were identified through a comprehensive search of electronic databases and specialised data repositories. The selection criteria included studies with a focus on gender-based violence, the use of closed-ended survey questions, i.e., in a questionnaire, the potential for applicability in different national contexts, and the specific context of higher education. Eligible sources also described the quantitative operationalisation of the survey measurements. Results Our work critically reviews previous efforts to measure gender-based violence, its determinants, and consequences in academic contexts. The findings of our assessment show, first, that quantitative gender-related measurements tend to conflate the concepts of sex and gender, and hence their operationalisation in quantitative surveys. Second, there is a strong emphasis on sexual harassment and sexual violence to the detriment of other relevant forms of violence, as well as a rooting of measurement concepts in locally valid but diverse legal definitions of gender-based violence. Third, there is a lack of socio-demographic determinants to provide an intersectional lens, as well as a focus on measurement frameworks that individualise the experiences of gender-based violence. This prevents a conceptualisation of harassment and abuse as a structural problem in the academic sector and ignores that violence is both as a cause and a consequence of unbalanced gendered power relations and inequalities in institutional and societal contexts. Fourth, there is generally a retrospective approach to measuring the consequences of gender-based violence, which may represent a source of potential bias. We reflect on how future survey instruments could address these issues in academic environments. Discussion Overall, our paper demonstrates how the evidence generated by different conceptualisations and operationalisations of gender-based violence in academia, as well as its determinants and consequences, shapes how we think and talk about the problem. In doing so, this article contributes to the ongoing methodological discussion on the measurement of gender-based violence and provides a rationale for improving its measurement framework in academic environments by taking a feminist-theory informed approach to collecting these data.